Perceptions and attitudes of public health service dentists in the face of family violence in 24 municipalities in the state of Sao Paulo, Brazil, 2013-2014 - Saliba Garbin, Clea Adas [UNESP]; Saliba Rovida, Tania Adas [UNESP]; Costa, Adriana Alves [UNESP]; Isper Garbin, Artenio Jose [UNESP] (Ministerio Da Saude, 2016)
Objective: to describe the perceptions and attitudes of dentists working in Primary Healthcare Units in the face of family violence in 24 municipalities in the interior of Sao Paulo state, Brazil. Method: this is a descriptive study conducted between July 2013 and July 2014; the study population was comprised of 294 professionals; data were collected through a questionnaire containing objective and subjective questions. Results: 111 dentists took part (37.8%), 67.5% of whom were unaware of existing legislation on cases of violence; 70.0% did not know how to report the occurrence of cases; 55.0% reported not having any responsibility for notification; 85.0% were unaware of the notification form; and 60.0% said they should intervene in cases of family violence. Conclusion: the perceptions and attitudes of dentists have shortcomings in relation to notification of family violence and this hinders early diagnosis of the victims of such violence.
Keywords: Domestic Violence; Epidemiology; Descriptive; Dentists; Forensic Dentistry